Hubungan Kadar Hb Pre Tranfusi Dengan Kualitas Hidup Penderita Talasemia Di Rsud Dr. Hi Abdul Moeloek Provinsi Lampung - Dea Prasetya (Malahayati Nursing Journal, 2021)
ABSTRACT: THE RELATIONSHIP OF PRE-TRANSFUSION HB LEVEL WITH QUALITY OF LIFE OF THALASSEMIA PATIENTS IN RSUD Dr. Hi ABDUL MOELOEK, LAMPUNG PROVINCE Background: Thalassemia is a chronic disease that can significantly affect the patient's quality of life, which is caused by the disease itself and the effects of the therapy given. Patients with thalassemia in Dr. H Abdoel Moeloek Hospital Lampung Province from year to year showed an increasing trend, namely in 2012 as many as 75 people, in 2013 as many as 87 people, and in 2014 as many as 102 people.Purpose: To determine the relationship between Hb levels before transfusion with the quality of life of thalassemia patients. Hi Abdul Moeloek Lampung ProvinceResearch Methods: This type of research is a quantitative, analytical observation design, with a cross-sectional design. The study population was all pediatric thalassemia patients at Dr. Hospital. Hi Abdul Moeloek, Lampung Province for the period January – October 2019 with a total of 146 patients. The sample is 60 people. Collecting data using observation sheets and questionnaires. The data analysis technique used a regression test.Results: The average distribution of Hb levels before transfusion of the research subjects was 7.11 with the lowest value being 6.8 and the highest being 7.4. The distribution of the average quality of life of the subjects of this study was 60.72 with the lowest value of 27 and the highest 93. There was a significant relationship between pre-transfusion Hb Levels and Quality of Life of Thalassemia Patients at Abdul Moeloek Hospital Bandar Lampung in 2019 (p-value 0.000 ).Conclusion: There is a significant relationship between Hb levels before transfusion with Quality of Life of Thalassemia Patients. It is recommended to monitor Hb levels before transfusion and comply with transfusions and consume iron chelation regularly so that the growth of their children can be normal like other children. Keywords: Hb levels before transfusion, Quality of Life, Thalassemia Patients  INTISARI: HUBUNGAN KADAR HB PRE TRANFUSI DENGAN KUALITAS HIDUP PENDERITA TALASEMIA DI RSUD Dr. Hi ABDUL MOELOEK PROVINSI LAMPUNG  Latar Belakang : Thalasemia adalah salah satu penyakit  kronis  yang  dapat mempengaruhi kualitas hidup penderita secara nyata, yang diakibatkan penyakitnya sendiri maupun efek terapi yang diberikan. Penderita thalasemia di RSUD Dr H Abdoel Moeloek Provinsi Lampung, dari tahun ketahun menunjukkan trend mengalami kenaikan, yaitu tahun 2012 berjumlah 75 orang, tahun 2013 berjumlah 87 orang dan tahun 2014  tercatat  102  orang.Tujuan penelitian:  Diketahui  hubungan kadar Hb Pre Transfusi dengan kualitas hidup penderita Talasemia Di RSUD Dr. Hi Abdul Moeloek Provinsi LampungMetode Penelitian : Jenis penelitian kuantitatif, rancangan observasi analitik, dengan desain cross sectional. Populasi penelitian adalah semua pasien Talasemia anak di RSUD Dr. Hi Abdul Moeloek Provinsi Lampung periode Januari - Oktober 2019 sejumlah 146 pasien. Sampel 60 orang. Pengambilan data menggunakan lembar observasi dan kuesioner. Teknik analisis data menggunakan uji regresi.Hasil penelitian : Distribusi rata-rata kadar Hb Pre tranfusi subyek penelitian ini adalah 7,11 dengan nilai terendah 6,8 dan tertinggi 7.4. Distribusi rata-rata kualitas hidup subyek penelitian ini adalah 60,72 dengan nilai terendah 27 dan tertinggi 93. Ada hubungan antara hubungan yang signifikan antara Kadar Hb Pre Transfusi Dengan Kualitas Hidup Penderita Talasemia di Rumah Sakit Abdul Moeloek Bandar Lampung tahun 2019 (p value 0,000).Kesimpulan : Ada hubungan antara hubungan yang signifikan antara Kadar Hb Pre Transfusi Dengan Kualitas Hidup Penderita Talasemia. Disarankan agar melakukan pemantauan terhadap Kadar Hb Pre Transfusi dan patuh menjalani tranfusi serta mengkonsumsi kelasi besi secara teratur agar pertumbuhan anaknya dapat normal seperti anak-anak lainnya. Kata Kunci    : Kadar Hb Pre Transfusi, Kualitas Hidup, Penderita Talasemia